2015
DOI: 10.1002/rcm.7287
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of glycopeptide esterification for the semi‐quantitative determination of sialylation in antibodies

Abstract: For antibody analysis, MALDI-MS ion abundances give a better semi-quantitative estimate of sialylation levels for esterified than for unreacted glycopeptides. The method is simple to use and helps to differentiate the branching patterns of sialic acids in antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…As minor species, non-sialylated G0F, G1F, and G2F glycoforms are completely suppressed in these spectra. Control experiments [53] showed that the suppression of G0F, G1F, and G2F relative to G2FS and G2FS2 is not due to loss of non-sialylated species from the sample due to heat or other experimental procedures. As the negative charge of sialic acid is neutralized through esterification, the positive mode mass spectrometric sensitivity of containing one underivatized sialic acid, b G2FSiaNAz1 containing one SiaNAz, c G2FS2 containing two underivatized sialic acids, and d G2FS1SiaNAz1 containing one underivatized sialic acid and one derivatized SiaNAz G2FS and G2FS2 increases, and thus, their abundances vs G0F, G1F, and G2F also increase.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As minor species, non-sialylated G0F, G1F, and G2F glycoforms are completely suppressed in these spectra. Control experiments [53] showed that the suppression of G0F, G1F, and G2F relative to G2FS and G2FS2 is not due to loss of non-sialylated species from the sample due to heat or other experimental procedures. As the negative charge of sialic acid is neutralized through esterification, the positive mode mass spectrometric sensitivity of containing one underivatized sialic acid, b G2FSiaNAz1 containing one SiaNAz, c G2FS2 containing two underivatized sialic acids, and d G2FS1SiaNAz1 containing one underivatized sialic acid and one derivatized SiaNAz G2FS and G2FS2 increases, and thus, their abundances vs G0F, G1F, and G2F also increase.…”
Section: Resultsmentioning
confidence: 97%
“…HPLC separation of glycopeptides Separation of glycopeptides was performed using a previously reported method [44,52] Esterification of glycopeptides This reaction was conducted according to a published method [53], adapted from conditions reported by Reiding et al for free glycans [54]. Briefly, 10-μg samples of tryptic mAb glycopeptides were reacted with HOBt and EDC, both 0.25 M in ethanol (10 μL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies have explored the feasibility of measuring deprotonated glycopeptides in negative ion mode with (130) and without (131) derivatization. Innovative strategies for the derivatization of sialic acid residues have also been designed to achieve linkage-specific (␣2,3 versus ␣2,6-sialyl) information at the glycopeptide level (132) and to obtain more equal ionization response from neutral and sialylated glycopeptides (133). Furthermore, attempts to generate universal workflows using Pronase digestion and C18-PGC LC-MS/MS instead of the conventional RP-LC-MS/MS of tryptic glycopeptides were described (39,134).…”
Section: Ms Acquisition Strategies In Glycoproteomics-lc-ms/mentioning
confidence: 99%
“…TKPREEQYNSTY and its fragments can be used for monitoring the progression of mAb digestion . Quantitation studies of EEQYNSTYR derivatives using MALDI–MS , HPLC–UV–MS , or esterification of the peptide followed by MALDI–MS/MS were carried out, although RP was employed.…”
Section: Analysis Of N‐ and O‐glycopeptidesmentioning
confidence: 99%